(untitled) (TAJ: Journal of Teachers Association, 2023)
Russell’s viper bite causing coagulopathy, hypotension, DIC, rhabdomyolysis and acute kidney injury. Nephropathy usually is caused by RV having hemotoxic or myotoxic venom components. Multiple mechanism causes renal pathologic changes including tubular necrosis, cortical necrosis, interstitial nephritis, and glomerulonephritis. But above all glomerulonephritis is very rare. We report a case of Russell’s viper bite who died of renal failure due to focal segmental proliferative glomerulonephritis admitted int the Rajshahi Medical College Hospital, Rajshahi, Bangladesh. TAJ 2022; 35: No-2: 169-172